The first high-redshift changing-look quasars. Issue 2 (2nd September 2020) - Ross, Nicholas P; Graham, Matthew J; Calderone, Giorgio; Ford, K E Saavik; McKernan, Barry; Stern, Daniel
ABSTRACT: We report on three redshift z > 2 quasars with dramatic changes in their C iv emission lines, the first sample of changing-look quasars (CLQs) at high redshift. This is also the first time the changing-look behaviour has been seen in a high-ionization emission line. SDSS J1205+3422, J1638+2827, and J2228 + 2201 show interesting behaviour in their observed optical light curves, and subsequent spectroscopy shows significant changes in the C iv broad emission line, with both line collapse and emergence being displayed on rest-frame time-scales of ∼240–1640 d. These are rapid changes, especially when considering virial black hole mass estimates of M BH > 10 9 M ⊙ for all three quasars. Continuum and emission line measurements from the three quasars show changes in the continuum-equivalent width plane with the CLQs seen to be on the edge of the full population distribution, and showing indications of an intrinsic Baldwin effect. We put these observations in context with recent state-change models, and note that even in their observed low-state, the C iv CLQs are generally above ∼5 per cent in Eddington luminosity.